Kaidah Hukum Jinayat Dalam Kitab Fathul Qorib Dan Relevansinya Terhadap Pembelajaran Kitab Di Pondok Pesantren Raudlatul Muhibbin Al-Mustainiyyah Surakarta - Octaviana Putri Ramadhani; Nadila Arya Dwi Saputri; Nisa Nur Mayanti; Airani Damayanti; Syalaisha Najma Fakhira Ibrohim (CV. SINAR HOWUHOWU, 2025)
This study aims to analyze the principles of jinayah law contained in Fathul Qorib and their relevance to the learning of classical Islamic texts at Pondok Pesantren Raudlatul Muhibbin Al-Mustainiyyah Surakarta. The background of this research lies in the prominence of Fathul Qorib as a fundamental fiqh reference in pesantren, particularly in shaping students’ understanding of Islamic criminal law and moral reasoning. This research employed a qualitative method with data collected through online interviews, observation of kitab learning activities, and documentation analysis involving the Fathul Qorib as the material object without further descriptive explanation. The findings indicate that Fathul Qorib presents systematic principles of jinayah law that emphasize justice, protection of human rights, and evidentiary requirements, making the kitab relevant for strengthening legal literacy and ethical formation among santri. The research also found that limitations in Arabic proficiency, time allocation, and traditional teacher-centered learning approaches reduce the effectiveness of jināyah learning in pesantren. Overall, this research contributes to the development of Islamic legal education by highlighting the importance of integrating classical fiqh texts with contemporary pedagogical innovations to ensure more contextual, applicable, and meaningful learning in pesantren environments.